The Mysterious Asteroid Apophis: Hazardous Asteroid, or Just a Passing Giant Space Rock? - Salem, Mohamed; Said, Mohamed; Osman, Hesham; El-Sedfy, Shahd; Abdellah, Nada; Ibrahim, Ahmed (International Journal of Advanced Astronomy, 2022)
Near-Earth asteroids (NEAs) are significant threat to Earth that have to be taken seriously. 99942 Apophis is a potentially hazardous NEA. The probability that Apophis would hit the Earth on April 13, 2029 is 2.7%. In this paper, a brief overview of the NEA Apophis is presented in order to highlight the risk of Apophis. In addition, this paper sounds the alarm to protect our planet from that threat or any other NEA.